Neuroprotective Effect of Danggui Shaoyao San via the Mitophagy-Apoptosis Pathway in a Rat Model of Alzheimer's Disease. (28th September 2021) - Song, Zhenyan; Luo, Deyong; Wang, Yuke; Zheng, Yushan; Chen, Peiying; Xia, Xiaofang; He, Chunxiang; Yu, Wenjing; Li, Ping; Xiao, Chen; Cheng, Shaowu
Abstract : Alzheimer's disease (AD) is a serious neurodegenerative disease. While the main pathological characteristic of AD is widely believed to be the accumulation of amyloid-beta (A β ) in neurons around neurofibrillary plaques, the molecular mechanism of pathological changes is not clear. Traditional Chinese medicine offers many treatments for AD. Among these, Danggui Shaoyao San (DSS) is a classic prescription. In this study, an AD model was established by injecting A β 1–42 into the brains of rats, which were then treated with different concentrations of Danggui Shaoyao San (sham operation; model; and Danggui Shaoyao San high-dose, medium-dose, and low-dose intervention groups). The Morris water maze test was used to assess the learning and memory abilities of the animals in each group. Nissl staining was used to detect neurons. Mitophagy was evaluated by transmission electron microscopy and immunofluorescence colocalization. Apoptosis was assessed by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay. The expression levels of autophagy- and apoptosis-related proteins were measured by western blot. Compared to the model group, the groups of AD rats administered medium and high doses of Danggui Shaoyao San showed significantly increased learning and memory abilities (P < 0.05 ), as well as significantly increased autophagosomes in the hippocampus. Moreover, the expression of PTEN-induced kinase 1 (PINK1), Parkin, and microtubule-associated protein light chain 3 (LC3-I/LC3-II) was increased, while that of p62 was significantly decreased (P < 0.05 ). The neuronal apoptosis rate was also significantly decreased, the Bcl-2/Bax ratio was significantly increased, and the cleaved caspase-3 protein expression was significantly decreased (P < 0.05 ). Therefore, Danggui Shaoyao San inhibited neuronal apoptosis in AD rats via a mechanism that may be related to the activation of the PINK1-Parkin-mediated mitophagy signaling pathway.